A importância da aquisição da língua de sinais na constituição humana da criança surda. - Reveilleau, Monique Giusti (2022)
The theme of this research is the importance of sign language as a way to guarantee the subjective constitution of the deaf child in language acquisition. Its general objective is to analyze the role of sign language as a way to guarantee the subjective constitution of the deaf child in language acquisition. In addition to this objective, it also intends to deepen the scientific knowledge around the work of Émile Benveniste, in order to better understand the concepts of language that underlie the work; reflect on the symbolic property that forms different languages and their human constitution; promote the discussion and raise awareness about the need to guarantee deaf children access to learning sign language as a first language. To do so, it utilizes the principles of language derived from Benveniste’s studies of enunciation (‘Énonciation’). For Benveniste (1989), enunciation encompasses the speaker's individual act of appropriating the language. This is a bibliographic study with narrative and case study research elements, informed by the experience of two deaf students from Colégio Estadual Joaquim Fagundes dos Reis and their relationship with sign language. It is important to highlight the fact that the researcher, the teacher of these students, is also deaf. Due to this singularity, the researcher’s account of the experience of sign language is present in the narrative research and leads the work as a whole. The investigation makes use of video interviews with students and their families, as well as data records. Rooted in the principles of Benveniste’s theory of enunciation, the analyses reveal the primordial importance of sign language in the human constitution of deaf individuals, given that it allows them to be integrated into society, an act that occurs through forming relationships with others and with that society’s culture.